Induction heating combined with antibiotics or SAAP-148 effectively reduces biofilm-embedded Staphylococcus aureus on a fracture-related implant mimic - Marielle Verheul; Anne A. Wagenmakers; Rob G. H. H. Nelissen; Peter H. Nibbering; Bart G. Pijls (Bone & Joint Research)
Aims: Fracture-related infections and the associated treatment failure burden our society and healthcare system significantly. As an alternative approach, we investigated the effect of non-contact induction heating (NCIH) against Staphylococcus aureus within mature biofilms. In addition, we assessed the ability of antibiotics, the antimicrobial peptide SAAP-148, and bacteriophage (phage) ISP to enhance the efficacy of NCIH, thereby allowing the use of lower temperatures during NCIH. Methods: Clinical isolates of methicillin-resistant and methicillin-sensitive S. aureus (methicillin-resistant S. aureus (MRSA), methicillin-sensitive S. aureus (MSSA)) were cultured for seven days on Ti-6Al-7Nb (mimicking fracture plates) discs to obtain mature biofilms. Biofilms were exposed to 60°C to 80°C NCIH. In addition, biofilms were sequentially exposed to 60°C to 70°C NCIH and rifampicin/ciprofloxacin, SAAP-148, or phage ISP. Biofilm-embedded bacteria were harvested by sonication to determine the bacterial load and visualized by confocal microscopy (LIVE/DEAD). Results: NCIH to 60°C, 70°C, and 80°C reduced biofilm-embedded MRSA and MSSA by 2.3-log, 4.9-log, 5.5-log, and 1.1-log, 3.4-log, and 6.6-log CFU/ml, respectively. LIVE/DEAD staining revealed NCIH-induced bacterial cell death throughout the biofilm layers. The sequential combination of rifampicin/ciprofloxacin at 10 µg/ml and 1,280 µg/ml (MRSA) or 156 µg/l and 64 µg/ml (MSSA) and 70°C NCIH synergistically reduced biofilm-embedded bacteria by 2.7-log and 3.7-log CFU/ml, respectively, while the alternating exposure order reduced bacterial counts by -0.1 and 1.7-log CFU/ml. SAAP-148 at 51.2 µM followed by 70°C NCIH further diminished biofilm-embedded MRSA and MSSA by 2.3-log and 1.5-log CFU/ml, respectively. No significant reductions were observed for NCIH combined with phage ISP compared to these treatments alone. Conclusion: NCIH effectively reduced biofilm-embedded S. aureus on Ti-6Al-7Nb in a heat-dependent fashion. Rifampicin/ciprofloxacin and SAAP-148, but not phage ISP, enhanced the efficacy of NCIH. Antibiotic exposure at suboptimal concentrations followed by NCIH was more effective than vice versa, suggesting that the application of this approach might be most suitable in clinical situations where antibiotic treatment has already started. Cite this article: Bone Joint Res 2025;14(5):485–494.